(untitled) (Journal of Enam Medical College, 2020)
Background: Inguinal hernia repair is one of the most common surgical procedures in Bangladesh. The option of surgical treatment remains controversial. Laparoscopic hernia repair has all the benefits of a tension free repair. We aimed to compare postoperative outcome and cost between laparoscopic and open inguinal hernia repair. Objective: This study was conducted with an objective to compare the effectiveness of each procedure and complications if any. Materials and Methods: Fifty cases of inguinal hernia admitted in the tertiary care center were selected by nonprobability (purposive) sampling method. All patients with uncomplicated hernia treated by open or laparoscopic method were included. The age/sex, incidence, mode of presentation, surgical treatment and postoperative complications were evaluated and compared with standard published literature. Results: Postoperative wound infection developed in three cases of open hernioplasty and one case in laparoscopic surgery. Hematoma and seroma at the operated site were found in one case of laparoscopic hernioplasty and in two cases of open hernioplasty. Orchitis was more prevalent in the laparoscopic hernioplasty patient with incidence among two cases as compared to one in open group. The mean duration of hospitalization was 59.62±6.11 hours in case of laparoscopic hernioplasty while 53.33±8.26 hours in open hernioplasty. The mean duration of procedure was 72.33 minutes in laparoscopic group while 64.62 minutes in open surgery. The mean cost for the laparoscopic repair group was around taka 63000/= whereas in the open group it was around 42000/= only with significant difference. Prolonged groin pain was seen in four cases in open group as compared to one in laparoscopically operated cases. Conclusion: There were less post-operative complications in the laparoscopic group. J Enam Med Col 2020; 10(1): 17-22